Development of simulation model & estimated accuracy for location determination technology (LDT) using enhanced observed time difference (E-OTD) / Muhd Zulfadli Ishammudin - Ishammudin, Muhd Zulfadli (2008)
Location related services are described as the next revolution on services and functionality in the mobile network. Location technology will help the operator to estimate the location of a mobile station in the network. But different location services require different accuracy of the location estimate. It is therefore important to find out what location method(s) is suitable for the operators needs. LBS are expected to spread rapidly due to the rapid growth of mobile devices. In future, the user of this service will be increased. Thus, the focus and objective of this paper is to understand about the services that exist in the LBS and to study about location determination of the MS in terms of the mobility (tracking/non-tracking), the time arrival and the radius of location detection. This report will give an overview of the most important location technologies for the GSM network on the market today and examples of the most common location services. It will also describe the network architecture needed to implement the E-OTD method. There is several mobile station positioning determination techniques for LBS. However, the focus of this dissertation is focusing on two methods of Location Determination Technologies (LDT), which are using E-OTD and TOA as comparison. The analysis for the TOA and E-OTD techniques was simulated using MATLAB 7.0. The development simulation model is purposely to estimate the accuracy of E-OTD based on error performance using a sample of channel model. Estimated accuracy using error magnitude of lxl0*6 s at 70% for TOA is at 330.3 metres and 257.7 metres for E-OTD. Therefore, simulation shows that the accuracy of E-OTD is higher than TOA technique